Functions of autophagy in chloroplast protein degradation and homeostasis - Wan, Chen; Ling, Qihua (Frontiers in Plant Science, 2022)
Chloroplasts are defining organelles in plant and algae, which carried out various critical metabolic processes, including photosynthesis. Roles of chloroplast protein homeostasis in plant development and stress adaptation were clearly demonstrated in previous studies, and its maintenance requires internal proteases originated from the prokaryotic ancestor. Recently, increasing evidence revealed that eukaryotic proteolytic pathways, ubiquitin-proteasome system (UPS) and autophagy, are also involved in the turnover of chloroplast proteins, in response to developmental and environmental cues. Notably, chloroplasts can be regulated via the selective degradation of chloroplast materials in a process called chlorophagy. Yet, understandings of the mechanism of chlorophagy are still rudimentary, particularly regarding its initiation and operation. Here we provide an updated overview of autophagy pathways for chloroplast protein degradation and discuss their importance for plant physiology. In addition, recent advance in analogous mitophagy in yeast and mammals will also be discussed, which provides clues for further studying the mechanism of chlorophagy.